MAPPING OF LITERATURE ON BOSE â€“ EINSTEIN CONDENSATION - Kademani, B. S.; Surwase, Ganesh; Sagar, Anil; Kumar, Vijai (Malaysian Journal of Library and Information Science, 2006)
This paper attempts to highlight quantitatively the growth and development of research work in this field on Bose-Einstein Condensation (BEC) in terms of publication output as per Science Citation Index (1982-2005). During 1982â€“2005 a total of 5258 papers were published by scientists in this field. The average number of publications per year were 219. The highest number of papers (814) were published in 2004. There were 77 countries involved in the research in BEC. USA is the top producing country with 1632 publications (31%) followed by Germany with 620 publications (11.79%). Authorship and collaboration trend was towards multiauthored papers. Intensive collaboration was found during 1996-2005. One paper â€œAstrophysical Journal 543 (1), (2000), L39-L42â€ had 56 collaborators. There were 1635 international collaborative papers. Bilateral collaboration accounted for 24 percent of total collaborative papers. National Institute of Standards & Technology (USA) topped the list with 179 publications followed by University of Colorado (USA) with 160 publications. The most prolific authors were W. Ketterle (USA) with 93 publications; K. Burnett (England) and M. Lewenstein (England) with 68 publications each; and S. Stringari with 57 publications. The most preferred journals by the scientists were Physical Review-A with 1504 papers; Physical Review Letters with 824 papers; Journal of Physics-B with 205 papers; Physical Review- B with 178 papers; Physics Letters-A with157 papers; Physical Reviewâ€“E with 122 papers; and Journal of Low Temperature Physics with 102 papers. The high frequency keywords were Bose-Einstein Condensation (2012), Gases (1928), Atoms (860), and Dynamics (493).